Prevalence, presentation and treatment of lower limb pathologies in juvenile idiopathic arthritis: A narrative review. (2nd August 2017) - Fellas, Antoni; Hawke, Fiona; Santos, Derek; Coda, Andrea
Abstract: Juvenile idiopathic arthritis is a chronic, autoimmune, inflammatory joint disease. It is the most common arthritis in children and adolescents. This paper reviews the presentation and treatment of lower limb pathologies in juvenile idiopathic arthritis from an allied health perspective. Common lower limb pathologies include: synovitis causing swelling, tenderness and pain; persistent inflammation leading to flexion contractures; limb length discrepancies; muscle atrophy; enthesopathies such as plantar fasciitis and Achilles tendonitis; and tenosynovitis. Allied health professionals may use a range of non‐invasive therapies, including hydrotherapy, strengthening and stretching exercises, massaging, taping and foot orthoses to manage lower limb pathologies in juvenile idiopathic arthritis. Early detection and treatment of these common and potentially disabling lower limb pathologies are fundamental to achieving gold standard care for children with juvenile idiopathic arthritis.